Sistem Monitoring Fluida Kompresor pada Timbangan Terigu Mill C di PT. Eastern Pearl Flour Mills - Ilham Septiansyach, Andi; Solihin, Ahmad; Ka’ka, Simon; Taufik, Akhmad (Jurnal Teknik Mesin Sinergi, 2025)
This research aims to develop a compressor fluid monitoring system based on the Internet of Things (IoT) for industrial weighing machines at PT. Eastern Pearl Flour Mills, supporting the implementation of Industry 4.0. The system is designed to monitor pressure, flow, and fluid temperature in real-time, enhancing the efficiency and reliability of machine operations. The research process includes the design of precise measuring instruments and a monitoring system utilizing ESP8266 and LoRa Ra-02 technology for data transmission. Fluid sensor data is processed and displayed via a web-based platform and an Android application. The study also involves sensor calibration to ensure accuracy, as well as system performance evaluation through experimental methods, user testing, and data analysis. The results of this research are expected to significantly improve process efficiency and control in weighing machines, providing a strong foundation for IoT technology implementation in operational management within the flour milling industry.